Development of Prone Position Ventilation Device and Study on the Application Effect of Combined Life Support Technology in Critically Ill Patients - Yufeng Li; Qiaoqiao Hu; Wenjie Wang; Changhong Du; Siwen Fan; Linlin Xu; Songmei Li; Bei Chen (Canadian Respiratory Journal)
Objective. This study aims to evaluate a novel prone position ventilation device designed to enhance patient safety, improve comfort, and reduce adverse events, facilitating prolonged tolerance in critically ill patients. Methods. A randomized controlled trial was conducted on 60 critically ill patients from January 2020 to June 2023. Of which, one self-discharged during treatment and another was terminated due to decreased oxygenation, leaving an effective sample of 58 patients. Patients were allocated to either a control group receiving traditional prone positioning aids (ordinary sponge pads and pillows) or an intervention group using a newly developed adjustable prone positioning device. A subset of patients in each group also received life support technologies such as extracorporeal membrane oxygenation (ECMO) and continuous renal replacement therapy (CRRT). We assessed prone position ventilation tolerance, oxygen saturation increments postintervention, duration of prone positioning, CRRT filter lifespan, and the incidence of adverse events. Results. The intervention group exhibited significantly longer average tolerance to prone positioning (16.6 hours vs. 8.3 hours, P<0.001 with a difference of 8.3 (4.4, 12.2) hours), higher increases in oxygen saturation postventilation (9% vs. 6%, P<0.001 with a difference of 3.0 (1.5, 4.5)), and reduced time required for medical staff to position patients (11.7 min vs. 21.8 min, P<0.001 with a difference of −10.1 (−11.9, −8.3)). Adverse events, including catheter displacement or blockage, facial edema, pressure injuries, and vomiting or aspiration, were markedly lower in the intervention group, with statistical significance (P<0.05). In patients receiving combined life support, the intervention group demonstrated improved catheter blood drainage and extended CRRT filter longevity. Conclusion. The newly developed adjustable prone ventilation device significantly improves tolerance to prone positioning, enhances oxygenation, and minimizes adverse events in critically ill patients, thereby also facilitating the effective application of life support technologies.